The last cuentista - Higuera, Donna Barba (Levine Querido, 2021)
When a comet destroys Earth, Petra Peña and her family are a few of the humans chosen to colonize a new planet for humanity. Hundreds of years later, Petra awakens and discovers that she is the only one who remembers Earth. While their ship traveled to the new planet, a sinister Collective took over, wiped the passengers' memories of humanity's sins, and purged all citizens who failed to comply. To fight back against the Collective, Petra must rely on her Mexican storytelling heritage and become a cuentista, or storyteller, like her grandmother in order to remind humanity of its past and save its future.